2019
DOI: 10.1021/acsami.8b20810
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Lysosomal Escape of pH-Responsive Polyethylenimine–Betaine Functionalized Carbon Nanotube for the Codelivery of Survivin Small Interfering RNA and Doxorubicin

Abstract: The combination of gene therapy and chemotherapy has recently received considerable attention for cancer treatment. However, low transfection efficiency and poor endosomal escape of genes from nanocarriers strongly limit the success of the clinical use of small interfering RNA (siRNA). In this study, a novel pH-responsive, surface-modified single-walled carbon nanotube (SWCNT) was designed for the codelivery of doxorubicin (DOX) and survivin siRNA. Polyethylenimine (PEI) was covalently conjugated with betaine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 40 publications
(79 reference statements)
0
36
0
Order By: Relevance
“…However, after review of this specialized area, we found that while the ribozyme approach was used for some time in research [111][112][113], further studies toward the use of this approach for cancer therapeutics were not progressing; this is likely due to the much easier approach of siRNA technology being available. Consistent with this notion, the survivin siRNA approach was used throughout the history of survivin studies [114][115][116][117][118]; the survivin siRNA studies in recent years show a clear trend of developing and using various new delivery technologies of survivin siRNA with or without combination of a cancer drug for therapeutics in vitro [119][120][121][122][123] and in vivo [124][125][126][127][128][129][130][131]. Although clinical trials using a type of nanotechnology to deliver survivin siRNA with or without combination of a cancer therapeutic drug remain to be seen, survivin siRNA formulated in a novel delivery system as an anticancer product will likely come into clinical trials in the near future.…”
Section: Inhibitors That Degrade Survivin Mrnamentioning
confidence: 98%
See 1 more Smart Citation
“…However, after review of this specialized area, we found that while the ribozyme approach was used for some time in research [111][112][113], further studies toward the use of this approach for cancer therapeutics were not progressing; this is likely due to the much easier approach of siRNA technology being available. Consistent with this notion, the survivin siRNA approach was used throughout the history of survivin studies [114][115][116][117][118]; the survivin siRNA studies in recent years show a clear trend of developing and using various new delivery technologies of survivin siRNA with or without combination of a cancer drug for therapeutics in vitro [119][120][121][122][123] and in vivo [124][125][126][127][128][129][130][131]. Although clinical trials using a type of nanotechnology to deliver survivin siRNA with or without combination of a cancer therapeutic drug remain to be seen, survivin siRNA formulated in a novel delivery system as an anticancer product will likely come into clinical trials in the near future.…”
Section: Inhibitors That Degrade Survivin Mrnamentioning
confidence: 98%
“…Whether the toxicity came from the unique locked modification of the EZN-3042 oligonucleotides, as discussed in the case of LY2181308, is unknown. Nevertheless, a breakthrough to find survivin mRNA inhibitors may come from the siRNA approach in combination with the development of nanotechnology for delivery [119][120][121][122][123][124][125][126][127][128][129][130][131], since survivin siRNA design in the coming years might take inspiration from various miRNA-mediated survivin mRNA inhibition. Currently miRNA regulation of survivin mRNA/transcripts is a hot research area, which has room for further in depth, extended studies (see Table 1) [146][147][148][149].…”
Section: Spc3042/ezn-3042mentioning
confidence: 99%
“…To overcome certain disadvantages of some pH-sensitive polymers, such as uncontrolled drug-loading or drug-releasing rate as well as undesired toxicity, non-polymer pH-sensitive carbon dots were also developed for cancer therapy [94]. In addition, recently surface modified pH-responsive SWCTs have also been developed to co-deliver anti-cancer drugs and genes [95].…”
Section: Ph-responsivementioning
confidence: 99%
“…The carrier was functionalized with polyethyleneimine (PEI) besides betaine. 93 Gemcitabine Also, Gemcitabine is among the anti-cancer drugs for nonsmall cell lung cancer. In a clinical trial on B6-mice, the drug was tested with an SWCNT carrier.…”
Section: Survivin Sirna and Doxorubicinmentioning
confidence: 99%